Association of Autosomal Dominant Polycystic Kidney Disease and Abdominal Aortic Aneurysm - A Case Report - Shterjova Markovska, Zhaklina; Rambabova Bushljetic, Irena; Severova Andreevska, Galina; Trajcheska, Lada; Nikolov, Igor; Karanfilovski, Vlatko; Usprcov, Julijana; Filipovski, Stefan; Canevska Taneska, Aleksandra; Dimova, Gabriela; Gjorgjievski, Nikola; Spasovski, Goce (Balkan Cities Association of Nephrology, Dialysis, Transplantation and Artificial Organs, 2023)
Introduction. Autosomal dominant polycystic kidney disease (ADPKD) is a systemic disease with multiple cysts in several organs. Formation of aneurysms of: the aorta, coronary and cerebral arteries are increasingly reported in the literature as extra-renal manifestations. Case report. We report a 77-year-old male with ADPKD and long-standing hypertension, admitted to our ward due to an extreme weakness, malaise and abdominal pain with severe anemia and elevated serum levels of creatinine and urea. The treatment with hemodialysis and blood substitution was initiated. Abdominal echo-sonography showed hepatic cysts and polycystic kidneys. The cysts were filled with a clear content, in the right kidney toward the upper pole, two larger cysts were noted and an adjacent pulsatile cystic lesion with a hemorrhagically-filled content, highly suspicious for an aneurismatically dilated abdominal aorta. CT angiography of the aorta showed dilated, tortuous aorta with advanced atherosclerosis along its entire length. The dilatation was evident in the descending part of the aorta, with an infrarenal saccular dilatation before the bifurcation, that seemed to be thrombosed and a denser content was observed next to it, probably an older hemorrhagy, without imaging signs of acute extravasation of the contrast. Cardiovascular surgeon recommended coronography and coronary artery aneurisms were excluded. Unfortunately, the patient started to alternate with his consciousness and brain CT angiography showed corticoreductive changes, without any aneurism, or extra-or intra-axial hemorrhage. Due to the severe general condition, clinical assessment and advanced age of the patient, the case was declared as inoperable. Conclusion. Due to a hypertension and associated connective tissue disorders patients with ADPKD are prone to develop aortic aneurysms, that should be questioned as a frequent feature in such patients. Hence, an early diagnosis and treatment decision based on a risk-benefit analysis, remain the cornerstone of management.